Modeling Syntactic Change under Contact: The Case of Italiot Greek - Guardiano, Cristina; Stavrou, Melita (Languages (Basel), 2021)
In this paper, we investigate patterns of persistence and change affecting the syntax of nominal structures in Italiot Greek in comparison to Modern (and Ancient) Greek, and we explore the role of Southern Italo-Romance as a potential source of interference. Our aim is to highlight the dynamics that favor syntactic contact in this domain: we provide an overview of the social context where these dynamics have taken place and of the linguistic structures involved.